"One nation, " BJP, and the future of Indian federalism. Issue 2 (14th March 2020) - Aiyar, Yamini; Tillin, Louise
ABSTRACT: On August 5 th 2019, the newly elected Bharatiya Janata Party (BJP) government in New Delhi moved the Indian Parliament to abrogate Article 370 and bifurcate the state of Jammu and Kashmir into two Union Territories. Months later, as the year came to a close, the Indian parliament passed a controversial amendment to India's Citizenship Law. Several state governments came out in vocal opposition to the amendment, and some challenged the amendment in the Supreme Court. These events provided confirmation that the reelection of a majority BJP government has heralded far-reaching changes for India's federal order, compounding shifts in the institutions and practice of federalism during Narendra Modi's first term (2014–19). In this article, we assess the implications of the 2019 Lok Sabha elections for the future dynamics of federalism in the constitutional, administrative, and fiscal spheres under the second term Modi government.